2005
DOI: 10.1007/s11295-005-0018-9
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite variability in apricots (Prunus armeniaca L.) reflects their geographic origin and breeding history

Abstract: A collection of 133 apricot cultivars and three related species originating from different geographical regions were studied with 10 polymorphic microsatellite markers developed in apricot. Altogether, 133 alleles were identified in the set of accessions, with an average of 13.30 alleles per locus. Out of them, 32 alleles occurred only once in the investigated samples, especially in apricots originating from different eco-geographic groups or in different species. The observed heterozygosity for individual loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
43
3
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 35 publications
8
43
3
1
Order By: Relevance
“…This result is in agreement with the study of Maghuly et al (2005) who reported that Cacansko zlato, Maďarská C-235, Velkopavlovická (Le 1) and Luizet 343 cultivars were localized in one subgroup. The same result was confirmed by Maghuly et al (2006).…”
Section: Genetic Relationships and Clustering Of Cultivars By Means Osupporting
confidence: 93%
See 3 more Smart Citations
“…This result is in agreement with the study of Maghuly et al (2005) who reported that Cacansko zlato, Maďarská C-235, Velkopavlovická (Le 1) and Luizet 343 cultivars were localized in one subgroup. The same result was confirmed by Maghuly et al (2006).…”
Section: Genetic Relationships and Clustering Of Cultivars By Means Osupporting
confidence: 93%
“…2, with Harogem, Leskora and Riland cultivars. Maghuly et al (2005) formed a group of cultivars of varied origin, among which were Orange Red, Harcot, Shalah, Churmai and Veecot.…”
Section: Genetic Relationships and Clustering Of Cultivars By Means Omentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, SSR markers have been widely used for molecular characterizations and similarity relationships among Prunus accessions and have revealed high polymorphism level to discriminate these accessions (Sosinski et al, 2000;Dirlewanger et al, 2002;Maghuly et al, 2005).…”
Section: Discussionmentioning
confidence: 99%